RESISTING COLONIALISM AND THE FORMATION OF ISLAMIC IDENTITY IN NUSANTARA-INDONESIA - Hajar, Imam Ibnu; Said, Imam Ghazali; Maram, Ahmad Nabilul (State Islamic University North Sumatra, 2025)
This study examines the impact of European colonialism on the political, economic, and religious identity dynamics of Muslim communities in the Nusantara while highlighting Islam’s role as a pillar of resistance. The research analyzes primary archives and secondary literature within a “Challenge and Response” framework using a historical-qualitative methodology. Findings show that Islamic sultanates had developed strong economic and cultural networks before European colonization. Policies of monopoly and cultural assimilation by the Portuguese and Dutch triggered resistance, marked by physical opposition and the reaffirmation of religious identity. Islamic institutions such as pesantren, ulama networks, and Sufi leaders were central in fostering solidarity and anti-colonial sentiments. Resistance spanned political, cultural, and spiritual domains, positioning Islam as an inspiration for social movements. This study concludes that colonialism accelerated the formation of Islamic identity as a resistance force, paving the way for structured liberation movements.